Consensus conference on the appropriateness of palivizumab prophylaxis in respiratory syncytial virus disease. Issue 10 (12th September 2016) - Pignotti, Maria Serenella; Carmela Leo, Maria; Pugi, Alessandra; De Masi, Salvatore; Biermann, Klaus Peter; Galli, Luisa; Vitali Rosati, Giovanni; Buonocore, Giuseppe; Mugelli, Alessandro; Dani, Carlo; Lucenteforte, Ersilia; Bellini, Francesca; et al.
Summary: Respiratory syncytial virus infection represents a clinical burden among young children under 24 months. Palivizumab is the only drug licensed in Italy for the prevention of serious lower respiratory tract disease requiring hospitalization caused by respiratory syncytial virus in children at high risk. However recommendations for palivizumab prophylaxis are heterogeneous. Not all the published documents agree about the clinical indications of palivizumab; this could lead to different clinical practices and concerns about the appropriateness of prophylaxis. These issues and the lack of evidence about palivizumab prophylaxis efficacy in specific medical conditions brought on the idea of a consensus conference on the current recommendations for the management and prevention of bronchiolitis, in order to share useful indications. The goal was to perform a review of the evidence regarding the efficacy and the safety of palivizumab and give recommendations in order to harmonize its use. A structured and validated method to conduct the consensus process was adopted. The consensus conference recommends palivizumab prophylaxis in infants born before 29 weeks and younger than 12 months at the start of the epidemic season. According to evidence from literature and experts' opinion, palivizumab prophylaxis is not recommended in preterm infants of gestational age ≥29 weeks, without co‐morbidity (i.e., cardiac, bronchopulmonary diseases). The experts identified some clinical rare conditions for which the decision of prophylaxis should be entrusted to the specialists. The evaluation of the appropriateness of palivizumab prophylaxis in the single patient should be documented by the specialists.Pediatr Pulmonol. 2016;51:1088–1096. © 2016 Wiley Periodicals, Inc.